PERAN KEPALA SEKOLAH SEBAGAI LEARNING DESIGNER DALAM MEMBANGUN EKOSISTEM PEMBELAJARAN DIGITAL DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of digital technology requires elementary school principals to shift their leadership paradigm from administrative orientation to digital instructional leadership. This study aims to describe the role of school principals as learning designers and analyze their strategies in building a digital learning ecosystem in elementary schools. This qualitative descriptive research was conducted at SDN 64 Kota Jambi, SDN 42 Kota Jambi, and SDN 106 Muaro Jambi, involving principals, teachers, and students as informants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles & Huberman interactive model. The findings reveal that principals have begun to demonstrate their role as learning designers through planning, organizing, and implementing basic digital learning initiatives. However, their focus is still limited to providing facilities and general guidance for teachers rather than designing comprehensive digital learning experiences. Schools are categorized as having moderate digital readiness, with unstable internet networks and limited projectors. Teachers’ use of digital media is present but inconsistent, and the digital culture has not been fully established. The study concludes that principals’ strategies need to be strengthened in designing systematic digital learning, developing teacher competencies, and conducting structured evaluations to support a sustainable digital learning ecosystem.